Comparação termométrica entre preparos cavitários realizados com turbinas de alta-rotação e laser de Er:YAG - Cavalcanti, Bruno das Neves [UNESP] (Universidade Estadual Paulista (Unesp), 2001)
The aim of this study was to compare temperature increases produced by a well-known equipment, the high-speed handpieces, with a relatively new instrument, the Er:YAG laser (350 mJ/10 Hz). Thirty-five bovine mandibular incisors, which were reduced to an enamel/dentin thickness of 2,5 mm, were used. Cavity preparation was done till a depth of 2, 5 mm. A thermocouple was placed to read the temperature inside of the pulp chamber. Analysis was performed in these groups: I - high-speed handpiece without water-cooling (n=10); II - high-speed handpiece with water-cooling (n=10); III - Er:YAG laser without water-cooling (n=5); IV- Er:YAG laser with water-cooling (n=10) Group III had only 5 teeth because it was impossible to properly make the cavity preparations by the laser equipment without water cooling. The temperature increases were recorded in a computer linked to the thermocouples and the data of the groups I, II and IV were submitted to Dunn's multiple comparison test (p<0,05). The medium temperature increases were: 11,64ºC for group I, 0,96ºC for group II, 40,86ºC for group III and 2,9°C for group IV. There were no statistical differences between groups lI and IV, and these were different from group I. The cavity preparations made by the high-speed and the laser equipment generated very similar heat increases under water-cooling. The water-cooling is essential to avoid aggressive temperature increases, both when using the high-speed and the laser equipment, and with laser it is especially necessary for ablation of enamel

O objetivo deste estudo foi comparar as variações de temperatura provocadas por turbinas de alta-rotação e pelo laser de Er:YAG (350mJ/10 Hz). Preparos cavitários classe V foram realizados numa profundidade de 2,0mm em 35 incisivos inferiores bovinos, que tiveram um termopar posicionado para ler as temperaturas no interior da câmara pulpar. A análise foi feita nos seguintes grupos: I - alta-rotação sem refrigeração a água; II - alta-rotação com refrigeração a água; III- laser de Er:YAG sem refrigeração a água; IV- laser de Er:YAG com refrigeração a água. Em todos os grupos foram utilizados dez dentes, com exceção do grupo III, que teve uma amostra de apenas cinco dentes, uma vez que foi impossível realizar os preparos adequadamente com o laser sem refrigeração. Os aumentos de temperatura foram gravados num computador ligados aos termopares e os dados dos grupos I, lI e IV foram submetidos ao teste de Dunn para comparações múltiplas (p<0,05). Os aumentos médios de temperatura foram: 11,64°C para o grupo I, 0,96°C para o grupo II, 40,86°C para o grupo lll e 2,9°C para o grupo IV. Não houve diferenças estatisticamente significantes entre os grupos II e IV, e estes foram diferentes do grupo I. Os preparos cavitários realizados com as turbinas de alta-rotação e com o laser de Er:YAG geraram aumentos de temperatura semelhantes quando sob refrigeração a água. A refrigeração é essencial para evitar aumentos de temperatura agressivos em ambos os casos e com o laser de Er:YAG é especialmente necessária para a ablação do esmalte
Keywords: Cavidade dentaria - Preparo; Lasers em odontologia; Esmalte dentário; Dental enamel